Hubungan Antara Dukungan Keluarga Terhadap Tingkat Kepatuhan Pengobatan Pasien Diabetes Melitus Tipe 2 Rawat Jalan di Rumah Sakit X Jakarta Periode Maret – April 2025 - Vidia Arlaini Anwar; Farida Tuahuns; Meyla Aulia Daffa Abdillah (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2025)
Type 2 diabetes mellitus is known as the mother of diseases because it can lead to various chronic complications if not properly managed. This disease is also among the top ten most common cases in the outpatient department of Hospital X Jakarta. The success of diabetes therapy highly depends on the patient’s adherence to long- term treatment, which is influenced by several factors, one of which is family support. When patients receive a high level of family support, it is expected that their treatment adherence will also be high. This directly contributes to the success of therapy, reflected in well-controlled blood glucose levels. Thus, patients with type 2 diabetes who maintain stable glucose levels can be considered to have achieved therapeutic goals. This study aims to determine the relationship between family support and treatment adherence among patients with type 2 diabetes mellitus at Hospital X Jakarta. This research uses a cross-sectional design and involves 120 respondents selected through quota sampling. The research instruments are the Henserling Diabetes Family Support Scale (HDFSS) and the ProMAS questionnaire. Data are analyzed using the Spearman rho test. The results show that most patients receive high levels of family support, and there is a significant relationship between family support and treatment adherence (p < 0.05). The most dominant type of family support provided is appreciation support. These findings indicate that the higher the family support received, the higher the level of treatment adherence, which contributes to therapeutic success.